Análisis del conocimiento del contenido en docentes de Matemáticas sobre el razonamiento Proporcional en un contexto rural de Quetame - Baquero Romero, Eilen Daniela (Universidad Antonio Nariño, 2025)
The objective of this research was to describe the specialized content knowledge on proportional reasoning used by fifth grade mathematics teachers in the rural area of the municipality of Quetame, Colombia. This study adopts a qualitative approach through the case study methodology, which allows a deep and contextualized understanding, it focuses on how educators understand mathematical concepts on proportional reasoning, it also analyzes how their own solution strategies can be teaching strategies